2014
DOI: 10.1242/jeb.102947
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythms affect the electroretinogram, compound eye color, striking behavior, and locomotion of the praying mantis,Hierodula patellifera(Serville)

Abstract: Many behaviors and physiological processes oscillate with circadian rhythms that are synchronized to environmental cues (e.g. light onset), but persist with periods of ~24 h in the absence of such cues. We used a multilevel experimental approach to assess whether circadian rhythms modulate several aspects of the visual physiology and behavior of the praying mantis Hierodula patellifera. We used electroretinograms (ERGs) to assess compound eye sensitivity, colorimetric photographic analyses to assess compound e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 66 publications
1
4
0
Order By: Relevance
“…We speculate that the disturbance in diurnal rhythm in our study may have resulted in an aberration in the shedding of outer segment disks, in turn leading to photoreceptor cell degeneration and attenuated ERG responses. In agreement with this are several studies that have shown a pivotal role for circadian rhythm in retinal function and ERG responses via melatonin and dopamine . In the turkey, photoperiod plays an important role in the regulation of melatonin .…”
Section: Discussionsupporting
confidence: 82%
“…We speculate that the disturbance in diurnal rhythm in our study may have resulted in an aberration in the shedding of outer segment disks, in turn leading to photoreceptor cell degeneration and attenuated ERG responses. In agreement with this are several studies that have shown a pivotal role for circadian rhythm in retinal function and ERG responses via melatonin and dopamine . In the turkey, photoperiod plays an important role in the regulation of melatonin .…”
Section: Discussionsupporting
confidence: 82%
“…The opsin expression of some insects follows a circadian rhythm and can be impacted by physiological and environmental factors, such as starvation or photoperiod [ 39 , 40 ]. Spectral sensitivity can also be impacted by environmental factors (e.g., illumination), as was demonstrated for the Mantidae Hierodula patellifera (Serville) [ 23 ] and the Lepidoptera Sphingidae Macroglossum stellatarum (Linnaeus) [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The maximum quantum flux of each tested wavelength was adjusted to approximately 10 11 ·photons·cm −2 ·s −1 by the light source regulator and neutral-density filters (Andover Corp., Salem, NH, USA). The spectral sensitivity was measured five times for each sex, from 17:00 to 20:00 during a day, to avoid the effect of circadian rhythms [ 23 ], with wavelengths alternating from 300 to 700 nm; then, the procedure was repeated in the reverse order, yielding ten spectral scans. The intensity output of the monochromatic light at each wavelength was calibrated by series of neutral-density filters.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the electrical activity of invertebrates' eyes (electroretinogram) and of the entire visual system display circadian fluctuations (Hernandez and Fuentes-Pardo, 2001). In the Praying Mantis, Hierodula patellifera, rhythms are associated with cyclic changes in the colour of the eyes, neural control of eye movement, and gross locomotor activity (Schirmer et al, 2014).…”
Section: Invertebratesmentioning
confidence: 99%